Pelatihan Pengelolahan Pelaporan Keuangan Di Warung Pecel Lele Pak Sani dan Warmindo Kapendak 02 - Desi Sari Abi; Diana Airawaty (BADAN PENERBIT STIEPARI PRESS, 2023)
This preparing program centers around upgrading monetary revealing administration abilities at Lele Pecel Pak Sani and Warmindo Kapendak 02. MSME proprietors will get exhaustive guidance on compelling monetary detailing works on, guaranteeing exactness and consistence with applicable guidelines. This drive expects to enable people participated in monetary detailing errands inside MSMEs, outfitting them with the information and abilities important to keep up with straightforward and dependable monetary records. At Lele Pecel Pak Sani and Warmindo Kapendak 02, MSME owners will improve their financial management by gaining valuable insights into financial reporting procedures through a combination of theoretical instruction and hands-on activities.